2006
DOI: 10.1063/1.2348881
|View full text |Cite
|
Sign up to set email alerts
|

W4 theory for computational thermochemistry: In pursuit of confident sub-kJ/mol predictions

Abstract: In an attempt to improve on our earlier W3 theory [A. D. Boese et al., J. Chem. Phys. 120, 4129 (2004)] we consider such refinements as more accurate estimates for the contribution of connected quadruple excitations (T4), inclusion of connected quintuple excitations (T5), diagonal Born-Oppenheimer corrections (DBOC), and improved basis set extrapolation procedures. Revised experimental data for validation purposes were obtained from the latest version of the Active Thermochemical Tables thermochemical network.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
1,132
1
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 735 publications
(1,171 citation statements)
references
References 72 publications
25
1,132
1
13
Order By: Relevance
“…In reference 17 we proposed a number of energy-based diagnostics for the importance of nondynamical correlation that are specifically designed for thermochemical purposes. In particular, the %TAE e [(T)] diagnostic, i.e.…”
Section: A Multireference Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In reference 17 we proposed a number of energy-based diagnostics for the importance of nondynamical correlation that are specifically designed for thermochemical purposes. In particular, the %TAE e [(T)] diagnostic, i.e.…”
Section: A Multireference Considerationsmentioning
confidence: 99%
“…It has been shown that highly accurate thermochemical protocols such as HEAT [14][15][16] and W4 17,18 are capable of sub-kJ/mol accuracy on average (see Ref. 19 for a recent review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] The Wn methods are more sophisticated and computationally expensive, with a typical accuracy of 0.5-1.0 kcal mol -1 . 23,25,26 Well-documented examples where the Gn and Wn families of model chemistries perform unreliably are for systems containing alkali and alkaline earth metal elements. A number of investigations of enthalpies of formation and cation affinities of s-block compounds provides the most egregious deviations for these otherwise successful composite methods.…”
Section: Introductionmentioning
confidence: 99%
“…21 There are other theories to predict accurate thermochemical data of chemical compounds. The correlation consistent composite approach (ccCA), 22-24 the complete basis set methods (CBS) [25][26][27][28] and the Weizmann theories (Wn), [29][30][31][32] are examples of alternatives to the gaussian-n theories.Theoretical Study of Thermochemical Properties using Composite Methods Adapted to ONIOM J. Braz. Chem.…”
mentioning
confidence: 99%